Enhanced radiation tolerance of YSZ/Al2O3 multilayered nanofilms with pre-existing nanovoids. (1st February 2018) - Wang, Hui; Ren, Feng; Tang, Jun; Qin, Wenjing; Hu, Lulu; Dong, Lan; Yang, Bin; Cai, Guangxu; Jiang, Changzhong
Abstract: Utilization of high density small sinks, such as voids, to collect and store helium atoms inside might be a potential new strategy for designing nanostructured materials with high radiation resistance to swelling and embrittlement. To understand the role of pre-existing nanovoids on irradiation, we investigated the evolutions of micro-structure and mechanical properties of the YSZ/Al2 O3 multilayered nanofilms irradiated by He + ions to different fluences. Compared to the Al2 O3 monolithic film and the single crystal bulk YSZ, smaller He bubbles were found in the Al2 O3 layers of the YSZ/Al2 O3 multilayered nanofilms with pre-existing nanovoids after He + ion irradiation. The growth of He bubbles was restricted inside the Al2 O3 layers to avoid the formation of large bubbles. In contrast to the radiation-induced hardening in traditional materials, radiation-induced softening is observed in the YSZ/Al2 O3 multilayered nanofilms with pre-existing nanovoids irradiated to high fluences. In addition, the hardness to Young's modulus (H/E) ratio of the YSZ/Al2 O3 multilayered nanofilms increases in response to irradiation, which suggests a potential improvement in the wear resistance of the irradiated YSZ/Al2 O3 multilayered nanofilms. A defect "loading-unloading" effect at the interfaces was proposed to explain the enhanced radiation tolerance. Graphical abstract: Image 1